Termodinamička analiza postupka zaštite prometnica soljenjem - Kancir, Boris (Promet - Traffic&Transportation, 2012)
On the defined model, the paper deals with the thermal dynamic analysis of functioning of the model of type H20- -NaCl protection mixtura making and the impact of condition changes of the obtained mixture upon tje reliability of the tangential friction force introduction and the factore of working the carriageway surface with the tires of teh givan vehicle.